MEMBANGUN CITRA POSITIF JEMBATAN PENYEBRANGAN ORANG MELALUI TEKNOLOGI TEPAT GUNA - Sri Dewi Setiawati; Veny Purba (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
The pedestrian bridge (JPO) is a public facility that has an important role in maintaining the safety of pedestrians. Unfortunately, many JPOs do not work optimally from their use, such as JPO on Jl. Merdeka in the city of Bandung. Road segment is a road segment that has a high traffic density and pedestrian high. JPO as a means of pedestrian safety for pedestrians, the current condition is apprehensive. Physically many JPOs are ultimately unkempt so it is not worth to be passed, other than that the number of crime actions that occur above the JPO makes JPO image worse. It requires a proper technology that will be able to build a positive image of JPO in the eyes of the public, such as Augmented reality (AR). So that society perception will change and society will always use JPO without forced. This research uses qualitative methodology, with case study method. The micro focus of this research is how to form positive perception through AR, how to form cognition through AR, how to form attitude to be able to interact with JPO through AR, how to form motivation interaction with JPO through AR. This research will get results that can be an example of socialization of government programs can be done through a more creative method.